Aster mayangheense (Asteraceae, Aster), a new species from Guizhou Province, China - Zhi Li; Jiang-hua Wu; Yu-jie Wang; Qi-xian Zhou; Ming-tai An (PhytoKeys)
Aster mayangheense Z.Li (Asteraceae, Astereae), a new species from Guizhou, China, is described and illustrated here. Morphological and molecular analyses based on nuclear ribosomal DNA internal transcribed spacer (nrDNA ITS) confirm its distinct status. The species is morphologically similar to A. saxicola, but differs by its falcate, adaxially shiny upper leaves 3.5–5.0 × 0.8–2.0 cm with long-acuminate to caudate apices (versus oblong-lanceolate to lanceolate leaves in A. saxicola); 5-seriate, abaxially red-purple phyllaries (versus 3–5-seriate with purple-tipped phyllaries); and fewer florets (7–12 ray florets and 5–9 disc florets versus 9–14 ray florets and 10–18 disc florets). Phylogenetic analysis strongly supports its distinctness, with four samples forming a monophyletic clade (PP = 1.00, BS = 100%) nested within Aster.